Integration of PCL and PLA in a monolithic porous scaffold for interface tissue engineering. (October 2016) - Scaffaro, Roberto; Lopresti, Francesco; Botta, Luigi; Rigogliuso, Salvatrice; Ghersi, Giulio
Abstract: A novel bi-layered multiphasic scaffold (BLS) have been fabricated for the first time by combining melt mixing, compression molding and particulate leaching. One layer has been composed by polylactic acid (PLA) presenting pore size in the range of 90–110 µm while the other layer has been made of polycaprolactone (PCL) with pores ranging from 5 to 40 µm. The different chemo-physical properties of the two biopolymers combined with the tunable pore architecture permitted to realize monolithic functionally graded scaffolds engineered to be potentially used for interface tissues regenerations. BLS have been characterized from a morphological and a mechanical point of view. In particular, mechanical tests have been carried out both in air and immersing the specimens in phosphate buffered saline (PBS) solution at 37 °C, in order to evaluate the elastic modulus and the interlayer adhesion strength. Fibroblasts and osteoblasts have been cultured and co-cultured in order to investigate the cells permeation trough the different layers. The results indicate that the presented method is appropriate for the preparation of multiphasic porous scaffolds with tunable morphological and mechanical characteristics. Furthermore, the cells seeded were found to grow with a different trend trough the different layers thus demonstrating that the presented device has good potential to be used in interface tissue regeneration applications. Graphical abstract: Highlights: Fabrication of bilayered scaffolds by melt mixing, molding and particulate leaching. The rigid PLA layer presents 100 µm pores size, the ductile PCL layer around 20 µm. Morphological and mechanical analysis showed an high interfacial adhesion strength. The whole compressive elastic behavior strongly depends on the PCL layer. Two cell lines showed different proliferation paths in co-culture.